2021
DOI: 10.2147/pgpm.s321997
|View full text |Cite
|
Sign up to set email alerts
|

Wuzhi Capsule Dosage Affects Tacrolimus Elimination in Adult Kidney Transplant Recipients, as Determined by a Population Pharmacokinetics Analysis

Abstract: Purpose In this study, we aimed to establish a tacrolimus population pharmacokinetic model and better understand the drug-drug interaction between Wuzhi capsule and tacrolimus in Chinese renal transplant recipients. Patients and Methods We performed a population pharmacokinetic analysis using a non-linear mixed-effects model to determine the suitable Wuzhi capsule dose in combination with tacrolimus. Data on 1378 tacrolimus steady-state concentrations were obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
3
4
0
Order By: Relevance
“…The CL/F of CYP3A5 non‐expressers (patients who have at least one function allele, CYP3A5*1 allele) was 2.38 h/L less than the expressers (homozygous for the variant allele, CYP3A5*3 allele). It was reported in one recently published study (Chen et al., 2021) that Wuzhi dose, CYP3A5*3 genetic polymorphisms were significant covariates for CL/F of tacrolimus; consistently, we observed the same results in this study. However, they also found Cr clearance rate and HCT as significant covariates in the final popPK model to characterize the PK of tacrolimus in Chinese kidney transplant recipients, which was inconsistent with our study that we did not investigate the correlations between CL/F of tacrolimus and Cr clearance rate, CL/F of tacrolimus and HCT.…”
Section: Discussionsupporting
confidence: 92%
“…The CL/F of CYP3A5 non‐expressers (patients who have at least one function allele, CYP3A5*1 allele) was 2.38 h/L less than the expressers (homozygous for the variant allele, CYP3A5*3 allele). It was reported in one recently published study (Chen et al., 2021) that Wuzhi dose, CYP3A5*3 genetic polymorphisms were significant covariates for CL/F of tacrolimus; consistently, we observed the same results in this study. However, they also found Cr clearance rate and HCT as significant covariates in the final popPK model to characterize the PK of tacrolimus in Chinese kidney transplant recipients, which was inconsistent with our study that we did not investigate the correlations between CL/F of tacrolimus and Cr clearance rate, CL/F of tacrolimus and HCT.…”
Section: Discussionsupporting
confidence: 92%
“…7,17,32 In the current study, we found a significant increase in TAC C 0 /D after co-administration with WZP. 33 Our findings are also consistent with previous study, 15 and we discovered that the fold changes in TAC C 0 /D prompted by WZP had a sizeable inter-individual variation of up to four or five fold.…”
Section: Discussionsupporting
confidence: 93%
“…36 A study from Chinese adult liver transplant recipients found that the effect of increasing age on The available literature confirms that the WZ capsule extract inhibits CYP3A in a concentration-and time-dependent inhibitory manner. 33 The effect of WZP on TAC C 0 is largely determined by WZP dosage. 19 Consistent with our previous study, 15 we found that the fold changes of C 0 /D increased with the dose of SchA in adult patients, but not in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Side effects, such as hyperkalaemia or fever, were reported after SchE and tacrolimus co-administration and were accounted for as a result of an increased tacrolimus blood concentration [ 78 , 86 ]. Several population pharmacokinetic models have been developed to support the individualization of tacrolimus dosing for different groups: renal transplant recipients [ 81 , 83 , 85 , 87 , 88 ], liver transplant recipients [ 89 , 90 ], cardiac transplant recipients [ 91 , 92 ], patients with refractory nephrotic syndrome [ 93 , 94 ], membranous nephropathy [ 95 , 96 ], lupus nephritis [ 97 , 98 ] or myasthenia gravis [ 99 ]. SchE may significantly increase tacrolimus bioavailability and reduce its therapeutic costs by 40–60%, nevertheless, authors highly recommend blood tacrolimus concentration monitoring while co-administering with SchE [ 78 , 79 , 82 , 85 ].…”
Section: Resultsmentioning
confidence: 99%